THE RELATIONSHIP BETWEEN DIFFERENTIATED INSTRUCTION AND ACADEMIC ACHIEVEMENT IN THE TEACHING OF ISLAMIC EDUCATION UNDER INDONESIA’S INDEPENDENT CURRICULUM - Asrori, Asrori; Riki Dwi Angga Saputro (Al-Mudarris, 2025)
This study aims to examine the relationship between differentiated instruction and students’ academic achievement in Islamic education within the framework of the independent curriculum. Differentiated instruction including content, process, and product differentiation is designed to accommodate student diversity in terms of readiness, interest, and learning profile. This study employed a quantitative correlational approach involving 120 eleventh-grade students at Madrasah Aliyah Tarbiyatut Tholabah, Lamongan. The research instruments included a differentiated instruction questionnaire based on Tomlinson’s framework and students’ end-of-semester Islamic education scores. The analysis revealed a significant positive correlation between differentiated instruction and academic achievement (r = 0.612, p < 0.001). Content differentiation was the strongest predictor of academic performance (β = 0.412), followed by process (β = 0.298) and product differentiation (β = 0.186). The regression model explained 42.3% of the variance in student achievement. These findings highlight the importance of integrating differentiated instruction into Islamic education and emphasize the need for strengthening teachers’ capacity to implement adaptive and inclusive teaching strategies.